What does the selfie say? Investigating a global phenomenon - Senft, Theresa M.; Baym, Nancy (International Journal of Communication, 2015)
Selfies are suddenly ubiquitous. In declaring selfie Oxford Dictionaries’ 2013 Word of the Year, Editorial Director Judy Pearsall explained that their big data analyses of English words in use showed “a phenomenal upward trend” in mentions of selfies (Oxford Dictionaries, 2013, para. 3). “Are you sick of reading about selfies?” asks an article in The Atlantic (Garber, 2014, para. 1), announcing that selfies are now boring and thus finally interesting. “Are you tired of hearing about how those pictures you took of yourself on vacation last month are evidence of narcissism, but also maybe of empowerment, but also probably of the click-by-click erosion of Culture at Large?” Indeed, for all its usage, the term—and more so the practice(s)—remain fundamentally ambiguous, fraught, and caught in a stubborn and morally loaded hype cycle.